Antiviral immune response as a trigger of FUS proteinopathy in amyotrophic lateral sclerosis - Shelkovnikova,TA; An,H; Skelt,L; Tregoning,JS; Humphreys,IR; Buchman,VL (Cell Reports, 2019)
Mutations in the FUS gene cause familial amyotrophic lateral sclerosis (ALS-FUS). In ALS-FUS, FUS-positive inclusions are detected in the cytoplasm of neurons and glia, a condition known as FUS proteinopathy. Mutant FUS incorporates into stress granules (SGs) and can spontaneously form cytoplasmic RNA granules in cultured cells. However, it is unclear what can trigger the persistence of mutant FUS assemblies and lead to inclusion formation. Using CRISPR/Cas9 cell lines and patient fibroblasts, we find that the viral mimic dsRNA poly(I:C) or a SG-inducing virus causes the sustained presence of mutant FUS assemblies. These assemblies sequester the autophagy receptor optineurin and nucleocytoplasmic transport factors. Furthermore, an integral component of the antiviral immune response, type I interferon, promotes FUS protein accumulation by increasing FUS mRNA stability. Finally, mutant FUS-expressing cells are hypersensitive to dsRNA toxicity. Our data suggest that the antiviral immune response is a plausible second hit for FUS proteinopathy.